SPACE Analysis: Strategies to Increase Capitation at Bunda Aminah Tambun Primary Clinic - Rian Pranata Pran; Henny Hanna (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
The purpose of this study is to analyze strategies to increase capitation at the Bunda Aminah Tambun Primary Clinic using the Strategic Position and Action Evaluation (SPACE) method with a quantitative descriptive approach through IFAS and EFAS analysis. One indicator of a clinic's success in the National Health Insurance (JKN) system is an increase in the number of capitation participants. The results of the study show that the Bunda Aminah Tambun Primary Clinic has a fairly strong internal condition (IFAS 3.13) and a supportive external condition (EFAS 3.07), despite facing very intense competition. Based on the SPACE Matrix analysis, the company is located in Quadrant I (Aggressive) with coordinates X = 3.00 and Y = 1.00. Therefore, the recommended strategy to increase clinic capitation is an aggressive one, focusing on market penetration, market development, and product/service diversification. This includes adding facilities, extending operational hours, or establishing corporate healthcare partnerships in industrial/residential zones within the Tambun area to achieve the expected capitation targets.